2001
DOI: 10.1034/j.1399-302x.2001.160603.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial flora of root canal–treated teeth associated with asymptomatic periapical radiolucent lesions

Abstract: This study aimed to investigate the composition of microflora in endodontically treated teeth associated with asymptomatic periapical lesions in southern Chinese patients. Twenty-four teeth which had received nonsurgical root canal treatment more than 4 years previously, and which presents an acceptable coronal restoration with a periapical radiolucent area, were re-treated nonsurgically. Bacteriological samples were obtained after removal of the old root canal filling. The samples were inoculated on enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 29 publications
9
84
1
5
Order By: Relevance
“…In consonance, at the baseline samples, the present study revealed the presence of cultivable bacteria in 100 % of the samples from endodontically treated teeth. The initial number of viable bacteria in post-treatment apical periodontitis ranged from 10 2 to 10 5 CFU/mL, which is comparable to previous investigations [7,26,27].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In consonance, at the baseline samples, the present study revealed the presence of cultivable bacteria in 100 % of the samples from endodontically treated teeth. The initial number of viable bacteria in post-treatment apical periodontitis ranged from 10 2 to 10 5 CFU/mL, which is comparable to previous investigations [7,26,27].…”
Section: Discussionsupporting
confidence: 84%
“…Controversies, exists on the use of solvent during endodontic retreatment [16,17,26]. Although solvents such as chloroform have been use to facilitate the process, their side-effects-i.e., cytotoxic potential and potential for forming a residual film of softened gutta-percha on the dentin walls-can overcome their benefits [17,26].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of enterococci has been a conspicuous finding in all studies that have investigated the flora in root-filled teeth, [51][52][53][54][55][56][57][58] with one exception, 59 and implicates Enterococcus faecalis as an opportunistic pathogen in persistent apical periodontitis.…”
Section: Microbiology Of Canals With Persistent Infectionmentioning
confidence: 99%
“…One species identified as a cause of persistent disease in endodontics is Pseudomonas aeruginosa (63)(64)(65)(102)(103)(104)(105) aeruginosa biofilms were susceptible to selected antibiotics and that increased resistance to antibiotic was typical of those that were grown for 48h or longer (147,149,150).…”
Section: Discussionmentioning
confidence: 99%
“…This method was chosen based on previous studies (6,31,60,63,65,104,132,155) that used paper points as their main method to extract the contents inside the root canal system. The paper points were specifically chosen to address the planktonic bacteria within the root canal.…”
Section: Discussionmentioning
confidence: 99%